Battery management systems. - Plett, Gregory L. (Artech House power engineering series., 2015)
Large-scale battery packs are needed in hybrid and electric vehicles, utilities grid backup and storage, and frequency-regulation applications. In order to maximize battery-pack safety, longevity, and performance, it is important to understand how battery cells work. This first of its kind new resource focuses on developing a mathematical understanding of how electrochemical (battery) cells work, both internally and externally. nThis comprehensive resource derives physics-based micro-scale model equations, then continuum-scale model equations, and finally reduced-order model equations. This book describes the commonly used equivalent-circuit type battery model and develops equations for superior physics-based models of lithium-ion cells at different length scales.nnThis resource also presents a breakthrough technology called the "discrete-time realization algorithm" that automatically converts physics-based models into high-fidelity approximate reduced-order models. n